IMPLEMENTASI METODE MANASIK HAJI TERHADAP PENINGKATAN KEMAMPUAN MELAKSANAKAN IBADAH HAJI DI KBIHU AL-HIKMAH SUKABUMI - Abdul Aziz Muslim; Heppi Permatasari (ADISAM PUBLISHER, 2025)
The main problem of this research is that the pilgrimage is a worship that is not performed all the time, this causes a low understanding of the pilgrims. Thus, it is necessary to have an effective Hajj ritual method to improve the ability to carry out the pilgrimage. This type of research is field research, with primary and secondary data sources. While the data collection techniques are observation, interviews, and documentation. The data analysis technique in this study is descriptive qualitative. The results of this study indicate an increase in the ability and understanding of pilgrims in carrying out the pilgrimage. The use of the method used by the Hajj and Umrah Guidance Group at KBIHU Al-Hikmah is in accordance with government directives through circular letter number: B-15.006/DJ/Dt.II.I/Hj.01/04/2019 covering, lecture method, questions and answers, discussions, visual video screenings and pilgrimage simulations, so that KBIHU Al-Hikmah has implemented the Hajj rituals method. Apart from this method, there are two methods used, namely the informal method by approaching the congregation such as chatting casually and the guidance method assisted by the role of the group leader. Even though it was able to increase the understanding and ability of pilgrims in carrying out the pilgrimage, this did not increase 100%. Because, in fact, when carrying out the pilgrimage in Saudi Arabia, pilgrims still need guidance from the Al-Hikmah Hajj and Umrah Guidance Group